Selangor govt has 30pc stake in Syabas, says KDEB - The Edge, Financial Daily (The Edge Financial Daily, 2013)
KUALA LUMPUR: Kumpulan Darul Ehsan Bhd (KDEB),the investment arm of the Selangor government, said the state government only has a minority stake limited to board representation in Syarikat Bekalan Air Selangor Sdn Bhd (Syabas). KDEB president Suhaimi Kamaralzaman said the state government only owns 30% equity interest and has two directors in Syabas.